Book Review. Issue 1 (1st June 2020) - Unknown
Abstract : Joseph Lacey, Centripetal Democracy: Democratic Legitimacy and Political Identity in Belgium, Switzerland, and the European Union (Oxford: Oxford University Press, 2017), 312 pp., ISBN: 9780198796886